Pemberdayaan masyarakat dalam membangun ketahanan pangan keluarga sebagai materi video edukasi di masa pandemi Covid-19 - Arifudin Arifudin; Khairul Anwar; Nita Rimayanti; Angga Pramana; Yogi Riyantama; M Sahal; Ahmad Haitami (Unri Conference Series: Community Engagement, 2020)
Household’s Food security during the Covid 19 pandemic, through the use of yards, can be conducted by the community independently such as hydroponic. However, people's understanding of hydroponic, especially in Pekanbaru, is still limited. Therefore, training for the community is needed as a community empowerment. These activities can be expanded through interesting educational videos. This community empowerment activity aims to increase community knowledge and skills regarding hydroponic technology during the pandemic, and is expected to become a post-pandemic household-scale economic enterprise. This community service activity is carried out by means of training and mentoring, as well as making a video to be widely disseminated through social media. The results of the community service activities show an increase in community knowledge and skills of hydroponic. After the training, the community independently has been aplicating hydroponic technology and biulding hydroponic group. This process is documented as educational video which is useful for the wider community in Pekanbaru City.